DIFFERENCES IN KINEMATIC PARAMETERS BETWEEN FIRST AND SECOND SERVES IN TENNIS BY ELITE PLAYERS OF THE GERMAN LEAGUE - Miran Pašić,; Tarik Huremović,; Melika Muratović,; Dževad Džibrić,; Amer Hodžić,; Davor Arnautović,; Aljoša Delić,; Miro Lušić, (Sport Scientific And Practical Aspects, 2025)
The primary goal of this research was to determine the differences in kinematic parameters between the first and second serves in tennis among the elite players of the German league. The sample of respondents in this research consisted of 30 elite male senior players of the German League who have "Leistungklasse" from 1 to 7. The kinematic parameters that were analyzed are: Height of ball impact (KPVUL), Racket speed (KPBRE), Ball speed (KPBLO), The angle at the elbow joint of the arm that hits the ball (KPULZ), Oscillation of the vertical projection of the center of gravity of the body (KPOVP), Jump height (KPVSK), Ball launch height (KPVIL), The point of contact between the ball and the racket "sweetspot" (KPMLR), Ball rotation "Top spin" (KPRLO). The video recording required for kinematic analysis was acquired with two Casio EX-F1 digital cameras at a frequency of 200 images per second. The camera was placed at an angle of 900 in relation to the recording plane, and they were at a distance of 10 m. Space calibration was performed with the help of a calibration frame (200 x 200 cm). We have installed Zepp Tennis Smart Sensor 2.0 in the handle of the Wilson Pro Staff RF97 Autograph racket, using the Zepp Tennis application software. "Kinovea" software was used for service analysis and obtaining kinematic parameters from video recordings. By analyzing the results of the T-test for independent samples, it can be seen that there are statistically significant differences in five of the nine analyzed kinematic parameters : KPBRE – kinematic parameter of racket speed (Sig.=.000), KPBLO – kinematic parameter of ball speed (Sig.=.000), KPULZ – kinematic parameter angle in the elbow joint (Sig.=.000), KPMLR – kinematic parameter point of contact between the ball and the racket (Sig.=.000), as well as a variable KPRLO – kinematic parameter of ball rotation (Sig.=.000). Larger numeric values in variables: KPVUL – kinematic parameter ball impact height, KPOVP – kinematic parameter of oscillation of the vertical projection of the center of gravity of the body, KPVSK – kinematic parameter jump height and KPVIL – kinematic parameter ball impact height, show a difference but it is not enough to be statistically different.